The decline of natural law : how American lawyers once used natural law and why they stopped - Banner, Stuart, 1963- (New York, NY : Oxford University Press, 2021)
In 'The Decline of Natural Law', Stuart Banner explores a fundamental change in the way American lawyers thought about the law. Until the late 19th century, lawyers understood the law in part as something found in nature, the way we think of scientific laws today. After the change, by contrast, lawyers understood the law as something entirely made by people, especially by judges. It explains the reasons for this change and how it affected the legal system.
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 10, 2021).
Keywords: Natural law; Common law; Religion and law; Law -- United States -- History